Legal Reform in the Enforcement of Illegal Fishing Crimes - Abdul Kamil Razak; Aloysius Wisnubroto; Tajudeen Sanni (Sekolah Tinggi Ilmu Hukum Adhyaksa, 2025)
Illegal, unreported, and unregulated (IUU) fishing is a growing threat to sustainable fisheries in Indonesia. This practice requires effective law enforcement, which raises the question: are fisheries regulations in Indonesia effective in enforcing measures to combat IUU fishing? This research aims to analyse the effectiveness of law enforcement in combating illegal fishing, analyse the implications of illegal fishing on sustainable fisheries development efforts, and design an ideal policy model for law enforcement in combating illegal fishing. This research applies a normative legal research method, utilising secondary data as the primary source of analysis. The approaches used include a legislative approach and a conceptual approach. This approach also serves as the foundation for formulating an ideal policy model to combat illegal, unreported, and unregulated (IUU) fishing. This study shows that, first, the fisheries legal system in Indonesia remains ineffective due to persistent weaknesses in legal substance, legal structure, and legal culture. Second, this ineffectiveness results in economic losses to the state, damage to the marine ecosystem, and a decline in the welfare of the community, especially those engaged in fishing. Third, there is a pressing need to renew the legal framework through harmonisation with international agreements, revision of the Fisheries Law to close legal gaps, institutional capacity building, and enhanced international cooperation as important steps towards establishing an effective, fair, and sustainable law enforcement model to protect Indonesia's marine resources for current and future generations.